The Effect of Subcontracted Labor Mix on Financial Performance: Evidence from High-Tech Project Teams - Avgerinos, Emmanouil; Momcheva, Antoaneta; Salvador, Fabrizio (INFORMS PubsOnline, 2022)
We investigate the effect of using subcontracted workers together with permanent employees on long and complex project’s financial performance. Academic/Practical relevance: Organizations are increasingly staffing project teams with subcontracted workers, in order to adapt to variations in demand and access specialist expertise. Despite the importance of this phenomenon, there is scant research on the effect of subcontracted workers on project performance. Investigating such an effect is important because past findings on the effects of subcontracting in retail or assembly lines cannot be simply extrapolated to the more demanding tasks associated to project environments. Methodology: We first develop a theoretical model to conceptualize how and under what conditions subcontracted workers impact project performance. We then test our hypotheses analyzing 413 projects of a European high-tech firm. Results: We find that greater use of subcontracted workers increases project profit margins. This positive effect becomes even more prominent as team size is increased. However, in projects with large scope changes, the positive effect of subcontracted workers is attenuated. Finally, we focus on the level of expertise of subcontracted workers and find that the positive effect on project performance is stronger for lower skilled subcontracted workers than for higher skilled ones. Managerial Implications: Our analysis shows that reliance on subcontracted workers in complex projects can positively impact project margins, especially for larger teams.
Keywords: Subcontracted labor mix; Project performance; Team size; Scope change; 53 Ciencias Económicas; ODS 1 - Fin de la pobreza; ODS 8 - Trabajo decente y crecimiento económico; ODS 10 - Reducción de las desigualdades